Parvovirus Encephalitis: Looking Through the Eyes - Maity, Debasis; Biswas, Arnab; Mitra, Sonali (Journal of Nepal Paediatric Society, 2020)
Parvovirus B19 usually causes less severe symptomatic infections. Its severity depends upon the affected cells of a particular organ system. Whereas diseases affecting the skin and haematological systems tend to be milder, affection of CNS may turn serious. Direct invasion or NS1 toxicity of Parvo virus B19 has been postulated behind CNS tropism. Here we depict Parvovirus B19 causing acute encephalitis and ophthalmoplegia in an immunocompetent male child, taking an eventful course, responded with IVIG & steroids, reversed the symptoms except some VEP abnormalities. This explores the need for timely intervention with immunotherapy in such cases to prevent permanent sequelae.